IMPLEMENTASI KAMPUS MENGAJAR UNTUK MENANAMKAN LITERASI BACA TULIS SISWA SEKOLAH DASAR - Tarisa Tarisa; F.Shoufika Hilyana; Much Arsyad Fardani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to explain the implementation of campus teaching in instilling reading and writing literacy. This research uses a qualitative approach with a case study design. The subjects in this study were fifth grade students, fifth grade homeroom teachers and university students teaching. Data collection techniques used in this study are observation, interviews and documentation. Data analysis techniques used in this study are data reduction, data presentation, and verification/conclusion. The results showed that the implementation of campus teaching in instilling literacy in reading and writing, namely reading fifteen minutes before learning began, daily reading journals and graphic organizers were effective to help students practice literacy skills.